2023
DOI: 10.1371/journal.pone.0279966
|View full text |Cite
|
Sign up to set email alerts
|

An expressway traffic congestion measurement under the influence of service areas

Abstract: Identifying traffic congestion accurately is crucial for improving the expressway service level. Because the distributions of microscopic traffic quantities are highly sensitive to slight changes, the traffic congestion measurement is affected by many factors. As an essential part of the expressway, service areas should be considered when measuring the traffic state. Although existing studies pay increasing attention to service areas, the impact caused by service areas is hard to measure for evaluating traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Abdel-Aty and Huang et al discussed drivers' choices when entering or leaving an on-ramp, and the results showed that in addition to the spacing between ramps, drivers' choices are infuenced by factors such as trip purpose, vehicle occupancy, driver income level, and E-Pass use [27]. Liao et al also considered the impact of service areas on expressway congestion [28].…”
Section: Infuencing Factorsmentioning
confidence: 99%
“…Abdel-Aty and Huang et al discussed drivers' choices when entering or leaving an on-ramp, and the results showed that in addition to the spacing between ramps, drivers' choices are infuenced by factors such as trip purpose, vehicle occupancy, driver income level, and E-Pass use [27]. Liao et al also considered the impact of service areas on expressway congestion [28].…”
Section: Infuencing Factorsmentioning
confidence: 99%